PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR MUATAN IPA TEMA 8 SUB TEMA 1 KELAS 4 - Anggistia Febby Fravitasari (Universitas Pendidikan Ganesha, 2018)
This study aims to improve the process and the results of learning content of science grade 4 students on the theme 8 Sub Theme 1 through the model of learning Problem Based Learning. This research is a classroom action research (PTK). The study was conducted in two cycles with three meetings each cycle. The subjects of the study were 4th grade students of SDN Mangunsari 05. The data collection techniques used in this classroom action research were test, observation, and documentation. Result of validity test at cycle I of 45 problem there are 26 valid questions, in cycle II there are 24 valid questions. Reliability test in cycle I obtained Cronbach's Alpha value of 0.904 and on the second cycle obtained Cronbach's Alpha value of 0.878. The learning process on the initial condition of teacher action is 78,57% and student action equal to 71,42%. In the first cycle of teacher action in the learning process of the first meeting 82.14%, the second meeting amounted to 89.28%. Student action on first cycle of first meeting is 75% and second meeting is 89.28%. In cycle II the teacher's first meeting action is 100% and the second meeting is 100%. Student actions in the first meeting process of learning amounted to 92.85% and the second meeting 100%. The result of the research shows that there is an increase of learning outcome of IPA especially the theme of 8 sub themes 1. It is proved by the increasing of learning result. At the time of initial condition of 30% of students who reach the threshold. In the first cycle there was an increase to 80% that reached completeness. While in the second cycle there is an increase to 100% which reached completeness. The conclusion of this research is the application of PBL learning model to make students become more active and courageous in solving problems and increasing the result of studying the content of science.Keywords: PBL Model, Process, Learning Outcomes